Diagnosing and managing diabetic somatic and autonomic neuropathy. (February 2019) - Azmi, Shazli; Ferdousi, Maryam; Kalteniece, Alise; Al-Muhannadi, Hamad; Al-Mohamedi, Abdulrahman; Hadid, Nebras H.; Mahmoud, Salah; Bhat, Harun A.; Gad, Hoda Y. A.; Khan, Adnan; Ponirakis, Georgios; Petropoulos, Ioannis N.; et al.
The diagnosis and management of diabetic neuropathy can be a major challenge. Late diagnosis contributes to significant morbidity in the form of painful diabetic neuropathy, foot ulceration, amputation, and increased mortality. Both hyperglycaemia and cardiovascular risk factors are implicated in the development of somatic and autonomic neuropathy and an improvement in these risk factors can reduce their rate of development and progression. There are currently no US Food and Drug Administration (FDA)-approved disease-modifying treatments for either somatic or autonomic neuropathy, as a consequence of multiple failed phase III clinical trials. While this may be partly attributed to premature translation, there are major shortcomings in trial design and outcome measures. There are a limited number of partially effective FDA-approved treatments for the symptomatic relief of painful diabetic neuropathy and autonomic neuropathy.